Posaconazole/hydroxypropyl-β-cyclodextrin host–guest system: Improving dissolution while maintaining antifungal activity. (20th May 2016) - Tang, Peixiao; Ma, Xiaoli; Wu, Di; Li, Shanshan; Xu, Kailin; Tang, Bin; Li, Hui
Highlights: Experimental methods and theoretical study are used to explore the HP-β-CD–POS complex. The water solubility of POS was increased by 82 times. Almost 90% of the loaded POS released after 10 min in the three dissolution media. The HP-β-CD–POS complex maintains high antifungal activities. Abstract: This study aimed to prepare and characterize the inclusion complex between posaconazole (POS) and hydroxypropyl-β-cyclodextrin (HP-β-CD). Phase solubility study was conducted to investigate the drug/CD interaction in solution, including the stoichiometry and apparent stability constant. The solid complex (HP-β-CD–POS) obtained was characterized through Fourier transform infrared spectroscopy, powder X-ray diffraction, 1 H and ROESY 2D nuclear magnetic resonance, differential scanning calorimetry, and scanning electron microscopy. These approaches confirmed the formation of the inclusion complex. The HP-β-CD–POS inclusion complex exhibited better water solubility and higher dissolution rate than the free POS did; the water solubility of POS was increased by 82 times and almost 90% of the loaded drug dissolved after 10 min in the dissolution media. In addition, preliminary in vitro antifungal susceptibility testing revealed that HP-β-CD–POS maintains a high level of antifungal activities. Therefore, the HP-β-CD complex may be useful in the delivery of posaconazole.